Recoverable nuclear pore structure MOF nano flame retardant and preparation method thereof

By coating the recyclable nuclear pore structure MOF nanofire retardant on the surface of polyurethane foam, the problems of melting droplets and smoke during combustion of foam materials are solved, and the flame retardant, smoke suppression and heat insulation effects are achieved, and the elasticity of the foam materials is retained. and sound insulation performance, while achieving the recycling of flame retardant, meeting the requirements of green and environmental protection.

CN119306964AActive Publication Date: 2025-01-14BEIJING INST OF TECH

Patent Information

Application Number
CN202411439896.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Flexible polyurethane foam produces a large amount of melting droplets and smoke when burning, which burns quickly, and the addition of existing flame retardant will damage the foam structure and be difficult to recycle, affecting life and property safety.

Method used

Using recyclable nuclear pore structure MOF nanofire retardant, holes are generated on the MOF surface through in-situ acid etching and phosphorus-nitrogen expansion flame retardant system, and foam surface coating and flame retardant separation are combined with alcohol dispersion to retain foam material original performance and achieve flame retardant effect.

Benefits of technology

It realizes the efficient flame retardant, smoke suppression and heat insulation effects of foam materials, retains the elasticity and sound insulation and noise reduction properties of foam materials, and realizes efficient separation and recycling of flame retardant and foam materials under ethanol soaking, which is in line with green and environmental protection. theme.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306964A_ABST
    Figure CN119306964A_ABST
Patent Text Reader

Abstract

The invention relates to a recyclable nuclear pore structure MOF nanometer flame retardant and a preparation method thereof, and belongs to the technical field of nanometer and flame retardant crossing. According to the MOF nano flame retardant with the nuclear pore structure, provided by the invention, after polyurethane foam is soaked in the high-concentration nano flame retardant, a foam material does not have a molten drop phenomenon, is self-extinguished after being away from fire and cannot be secondarily ignited, and the foam material shows good flame-retardant and heat-insulating effects and is outstanding in smoke suppression effect. And after being introduced into the foam material, the foam material has improved elasticity, and the nuclear pore structure endows the foam material with higher sound insulation and noise reduction effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a recyclable core-pore structure MOF nanoflame retardant and its preparation method, belonging to the interdisciplinary field of nanotechnology and flame retardants. Background Technology

[0002] Flexible polyurethane foam (FPUF) is widely used in transportation, furniture, vehicle seating, and construction industries due to its excellent thermal insulation and high resilience. FPUF contains block copolymers, and its toughness is based on phase separation between soft and hard segments. Its internal structure has numerous open pores, providing good flexibility and user comfort. However, foam materials are easily ignited, producing large amounts of molten droplets and smoke (such as CO, NOx, and HCN). Furthermore, due to its large specific surface area, its burning rate is much faster than other polymer materials, increasing the difficulty of fire rescue and seriously threatening people's lives and property. Adding flame retardants during the foaming process is an efficient and convenient solution, but this process often requires large amounts of flame retardants (above 20 wt%), which usually damages the foam structure, leading to a loss of the foam's high elasticity, and flame retardants are generally difficult to recycle. Therefore, it is necessary to construct an efficient flame-retardant system for flexible polyurethane foam that can retain its original properties.

[0003] Research on foam materials has revealed that surface coating of polyurethane foam is a way to preserve the material's mechanical properties and improve its flame retardant performance. Furthermore, numerous studies have shown that introducing nanomaterials into polymer matrices can preserve or enhance their original mechanical properties, providing a solution for maintaining the high resilience of polyurethane foam. Metal-organic frameworks (MOFs), as a novel type of nanomaterial, have already found applications in sensors, gas adsorption, catalysis, and drug delivery due to their flexibility in composition and structure. Existing research has confirmed that surface modification of polymer matrices using MOF materials can endow the materials with numerous superior properties, providing a new direction for flame-retardant polyurethane foam. MOF nanomaterials can be dispersed in aqueous solutions for foam surface coating, and post-processing using benign dispersions such as alcohols can separate the foam and flame retardants, enabling the recycling of both materials and aligning with green environmental protection principles.

[0004] However, research has confirmed that the contribution of existing MOF materials to the flame retardancy of polymers is negligible. Appropriately combining MOFs with flame-retardant organic ligands represents a new direction for flame retardant development. Combining MOF nanomaterials with traditional flame-retardant ligands (where the ligands need to possess certain acidity or alkalinity) allows for the integration of active metals in the MOF raw materials, flame-retardant elements in the ligand flame retardants, and the unique nanostructure of MOFs, achieving excellent flame retardant and smoke-suppressing effects. However, existing modified MOF materials mostly have core-shell or hollow structures, which pose certain drawbacks for the adsorption of toxic gases during combustion. Therefore, it is necessary to prepare a novel MOF material with a core-pore structure to achieve efficient adsorption of toxic gases and thus achieve the desired flame retardant and smoke-suppressing effects. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of the existing technologies described above by proposing a recyclable core-pore structure MOF nano-flame retardant and its preparation method. This method involves a slow etching process using an ice-water bath to prepare MOF nanomaterials, resulting in the synthesis of a core-pore structure MOF nano-flame retardant. This invention utilizes an in-situ acid etching method to generate HCl on the MOF surface for pore etching and introduces a phosphorus-nitrogen expansion flame retardant system, optimizing the flame retardant effect and gas adsorption capacity of the MOF material itself. Using an immersion coating method, the flame retardant is ultrasonically dispersed in water and then coated onto the surface of polyurethane foam, greatly ensuring the excellent performance of the foam material. In the subsequent flame retardant recovery process, this invention employs an alcohol immersion method, achieving efficient separation of the flame retardant from the polymer matrix. This is of great significance for green nano-flame retardants and broadening the application range of materials.

[0006] The objective of this invention is achieved through the following technical solution.

[0007] A recyclable core-pore structure MOF nanoflame retardant is disclosed. The nanoflame retardant has a core-pore structure with an internal core and an external pore structure. Due to the introduction of an acidic system, in-situ etching was achieved on the surface of ZIF-67, which expanded the pores on its surface into a mesoporous structure. The nanoflame retardant retains the original metal framework structure of ZIF-67. Its internal core is a solid organic-inorganic hybrid core, mainly composed of Co and N elements, and its external core is loaded with acidic components mainly composed of P and N elements.

[0008] A method for preparing a core-pore structured MOF nanoflame retardant, the specific steps of which are as follows:

[0009] Step 1: First, dissolve a certain amount of 2-methylimidazole in methanol, and denote this as solution A;

[0010] Dissolve cobalt nitrate hexahydrate in the same volume of methanol and denote it as solution B;

[0011] Solution A was slowly added dropwise to solution B, and the solution settled at room temperature to form nuclei. The supernatant was removed by centrifugation and dried in a vacuum oven to obtain purple ZIF-67 powder.

[0012] Step 2: Take a certain amount of purple ZIF-67 powder in methanol or ethanol, and ultrasonically disperse it until there are no obvious particles. The resulting purple liquid is denoted as solution C. Place solution C in a refrigerator (4℃~10℃) to cool down for later use.

[0013] Step 3: Weigh out the gel-state hydroxyethyltriazine and disperse it in methanol. Sonicate it for 30-50 min until it is completely dissolved. Add spirocyclic phosphoric acid chloride (SPDPC) as a phosphorus source and sonicate it for 1-1.5 h. This solution is denoted as solution D (pH between 1 and 5).

[0014] Step four: Add solution D dropwise to solution C through a constant pressure dropping funnel. The temperature of solution C is controlled by an ice-water bath at 5-10°C to mimic wind erosion in real life. Control the dropping rate of solution D and slowly add it. Continue the ice-water bath reaction until it is finished. Centrifuge to remove the supernatant, wash with ethanol several times, and then vacuum dry to obtain a blue-purple powder, which is the core-pore structure MOF nano flame retardant.

[0015] In step one, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 4-8:1; the ratio of 2-methylimidazole to methanol is 1g:60-120mL; the ratio of cobalt nitrate hexahydrate to methanol is 1g:60-120mL; the vacuum drying pressure is 0.08-0.1MPa, and the temperature is 60-70℃.

[0016] In step two, the ultrasonic dispersion time is 10-30 min; the ratio of purple ZIF-67 powder to methanol or ethanol is 1 g: 150-200 mL.

[0017] In step three, the molar ratio of hydroxyethyltriazine to spirocyclic phosphoric acid chloride (SPDPC) is 2-2.2:3; the ratio of hydroxyethyltriazine to methanol is 1g:60-120mL.

[0018] In step four, the temperature of the ice-water bath needs to be controlled between 5 and 10°C. If it exceeds this range, ZIF-67 will exhibit over-etching and will not have the core-shell characteristic structure. The mass ratio of hydroxyethyltriazine to ZIF-67 is 1:0.5-0.8.

[0019] Solution D was added dropwise over a period of 1–4 hours; after the addition was complete, the reaction was continued in an ice-water bath for 3–6 hours.

[0020] Beneficial effects

[0021] 1. This invention provides a core-porous MOF nano flame retardant, which differs from existing preparation methods. It proposes a novel structured ZIF nanomaterial prepared by mimicking wind erosion phenomena in real nature. It has good mass transfer and thermal conductivity and a high decomposition temperature. The core-porous MOF nano flame retardant provided by this invention is a novel green and environmentally friendly flame retardant that can be recycled. It can separate the flame retardant from the foam material by soaking in ethanol, which is in line with the current theme of green environmental protection.

[0022] 2. The present invention provides a core-pore structure MOF nano flame retardant. After polyurethane foam is soaked in a high concentration of nano flame retardant, the foam material no longer exhibits melting and dripping phenomena and is self-extinguishing after being removed from the flame. It cannot be re-ignited, and the foam material exhibits good flame retardant and heat insulation effects and outstanding smoke suppression effect.

[0023] 3. The MOF nano flame retardant with a core-pore structure provided by the present invention benefits from its novel core-pore morphology. After being introduced into foam materials, the elasticity of the foam materials is improved. In addition, its core-pore structure gives the foam materials a higher sound insulation and noise reduction effect. Attached Figure Description

[0024] Figure 1 Transmission electron microscopy images and elemental contents of the ZIF@PST nano flame retardant synthesized in this invention;

[0025] Figure 2 The X-ray diffraction pattern of the ZIF@PST nano flame retardant synthesized in this invention;

[0026] Figure 3 Compression cycle test for blank FPUF foam;

[0027] Figure 4 The load-displacement diagram is shown for the FPUF-ZIF@PST prepared by this invention after ten compression cycles. Detailed Implementation

[0028] The following examples, based on experimental results of the present invention, are provided to further illustrate the present invention.

[0029] Example 1

[0030] A method for preparing a core-pore structured MOF nanoflame retardant, the specific steps of which are as follows:

[0031] Step 1: ZIF-67 with a typical dodecahedral structure was prepared by dissolving the reactants in methanol and allowing it to stand at room temperature for 24 hours. First, 95.36 g (0.48 mol) of 2-methylimidazole was dissolved in 500 mL of methanol solution, designated as solution A. 17.46 g (0.06 mol) of cobalt nitrate hexahydrate was dissolved in the same volume of methanol solution, designated as solution B. Solution A was slowly added dropwise to solution B, and the mixture was allowed to settle and nucleate at room temperature for 24 hours. The supernatant was removed by centrifugation, and the solution was dried in a vacuum oven at 70°C (0.1 MPa) to obtain purple ZIF-67 powder, with a yield of 22.3%. ZIF-67 prepared under these conditions was more uniform, resulting in more homogeneous etching nanomaterials.

[0032] Step 2: Take 3g of ZIF-67 powder in ethanol solvent and ultrasonically disperse until no obvious particles are visible, resulting in a purple liquid, denoted as solution C. Place it in a refrigerator (4℃~10℃) to cool and store for later use. Weigh 6g of gel-state hydroxyethyltriazine and disperse it in ethanol, ultrasonically treat for 30min until completely dissolved, add 8.13g of SPDPC as a phosphorus source and ultrasonically disperse for 1h, denoted as solution D (acidic, pH between 1 and 3), and transfer it to a constant pressure dropping funnel. Using an ice-water bath, control the reaction temperature at 5~10℃, mimicking the wind erosion phenomenon in real life, control the dropping rate of solution D, and slowly add it for 3h. After completion, continue the ice-water bath reaction for 6h until finished. Centrifuge to remove the supernatant, wash several times with ethanol, and vacuum dry at 70℃ (vacuum degree 0.1MPa) to obtain a blue-purple powder, which is the core-pore structure MOF nano flame retardant ZIF@PST, with a yield of 85.3%.

[0033] Example 2

[0034] A method for preparing a core-pore structured MOF nanoflame retardant, the specific steps of which are as follows:

[0035] Step 1: Similar to Example 1, this step involved a scale-up experiment under the same conditions. The reactants were dissolved in methanol, and ZIF-67 with a typical dodecahedral structure was prepared by allowing it to stand at room temperature for 24 hours. First, 190.72 g (0.96 mol) of 2-methylimidazole was dissolved in 1000 mL of methanol solution, designated as solution A. Then, 34.92 g (0.12 mol) of cobalt nitrate hexahydrate was dissolved in the same volume of methanol solution, designated as solution B. Solution A was slowly added dropwise to solution B, and the mixture precipitated and nucleated at room temperature for 24 hours. The supernatant was centrifuged to remove the nucleus, and the powder was dried in a vacuum oven at 70°C (0.1 MPa) to obtain purple ZIF-67 powder with a yield of 25%. Under these conditions, the ZIF-67 prepared had a higher yield and more uniform particle size, resulting in more uniform etching nanomaterials.

[0036] Step 2: Take 6g of ZIF-67 powder in ethanol solvent and ultrasonically disperse until no obvious particles are visible, resulting in a purple liquid, denoted as solution C. Place it in a refrigerator (4℃~10℃) to cool and store for later use. Weigh 12g of gel-state hydroxyethyltriazine and disperse it in ethanol, ultrasonically treat for 1h until completely dissolved, add 16.26g of SPDPC as a phosphorus source and ultrasonically disperse for 1h, denoted as solution D (acidic, pH between 1 and 3), and transfer it to a constant pressure dropping funnel. Use an ice-water bath to control the reaction temperature at 5~10℃, mimicking the wind erosion phenomenon in real life, and control the dropping rate of solution D, slowly adding it for 4h. After completion, continue the ice-water bath reaction for 6h until finished. Centrifuge to remove the supernatant, wash multiple times with ethanol, and vacuum dry at 70℃ (vacuum degree 0.1MPa) to obtain a blue-purple powder, which is the core-pore structure MOF nano flame retardant ZIF@PST, with a yield of 92.3%.

[0037] To characterize the structure of the obtained core-pore MOF nanoflame retardant ZIF@PST, transmission electron microscopy (TEM) and X-ray diffraction (XRD) spectroscopy were performed. The TEM results are as follows: Figure 1 As shown, the MOF nano-flame retardant ZIF@PST nano-flame retardant exhibits a distinct core-pore structure, with P appearing in the elemental spectrum while retaining the original Co element. XRD results are shown below. Figure 2 As shown, this core-porous MOF nanoflame retardant ZIF@PST retains the characteristic crystal plane structure of ZIF-67 and exhibits a good crystal structure. Thermogravimetric analysis (TGA) was performed on the obtained core-porous MOF nanoflame retardant ZIF@PST, and the results showed that its decomposition temperature was between 500 and 650 °C, demonstrating excellent thermal stability.

[0038] Preparation method of polyurethane foam coated with MOF nano flame retardant: The ZIF@PST nano flame retardant prepared in Example 2 was coated on the surface of polyurethane foam and soaked multiple times to obtain surface-modified flame-retardant polyurethane foam. First, the polyurethane foam was washed twice and then cut to the corresponding size for later use. The ZIF@PST flame retardant (1g, 3g, 5g) prepared above was dispersed in 100mL of water and ultrasonically treated for 10min. The foam was then soaked in the above solution for 10min and then pressed repeatedly to re-adsorb. The above steps were repeated three times. The foam was dried in a 70℃ forced-air oven for 12h to obtain polyurethane foam coated with ZIF@PST flame retardant, with a mass increase of 0.038g, 0.067g, and 0.15g respectively, thus preparing FPUF-ZIF@PST-1, FPUF-ZIF@PST-3, and FPUF-ZIF@PST-5 foam materials. Combustion tests revealed that after soaking in a 5% concentration of nano-flame retardant, the foam material no longer exhibited dripping and became self-extinguishing upon removal of the flame, preventing secondary ignition. Its limiting oxygen index reached 30.1%. Adding this flame retardant reduced the peak heat release rate of the polyurethane foam by 52.3%, carbon dioxide production by 42.5%, and carbon monoxide production by 39.3%, demonstrating significant smoke suppression. Furthermore, its compression cycle images are shown below. Figure 3 and Figure 4 As shown, the soaked polyurethane foam material retains its original volume and its elastic modulus increases to 1.6523 MPa compared to the original foam material; its core-pore structure gives the foam material a higher sound insulation and noise reduction effect, and the sound insulation of sound waves above 2000 Hz is more than twice that of the original foam material (original foam 2.12~3.38 dB / 1, new foam 4.99~8.00 dB / 1).

[0039] Recovery and separation of polyurethane foam and flame retardant: The obtained FPUF-ZIF@PST-5 foam material was immersed in an ethanol solution. Due to the higher density of the modified foam than ethanol, it sank in the ethanol solvent. After standing for 30 minutes, the ethanol solvent turned blue, and the foam material returned to its white color. The foam material was transferred to a fresh ethanol solvent, and the immersion was repeated until no blue color appeared (this was achieved in three attempts). The blue ethanol was then subjected to rotary evaporation to obtain 0.136g of the original flame retardant ZIF@PST, achieving a recovery rate of 91%. The foam material remained unchanged in weight and could be reused, achieving a circular and environmentally friendly effect.

[0040] The above detailed description further illustrates the purpose, technical solution, and beneficial effects of the invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A recyclable nuclear pore structure MOF nano flame retardant, characterized in that: The nano flame retardant has a core-pore structure, with a core inside and holes outside; The interior is a solid organic-inorganic hybrid core, mainly composed of Co and N elements; Acidic components mainly composed of P and N elements are loaded externally.

2. A method for preparing a nuclear pore structure MOF nano flame retardant, characterized in that The steps of the method include: Step 1: 2-methylimidazole and methanol are mixed to obtain solution A, and cobalt nitrate hexahydrate and methanol are mixed to obtain solution B; solution A is added dropwise to solution B, and the solution is precipitated at room temperature to form nuclei, the supernatant is removed by centrifugation, and the ZIF-67 powder is obtained by vacuum drying; Step 2, adding the ZIF-67 powder obtained in step 1 into methanol or ethanol, and dispersing by ultrasonication to obtain solution C; Step 3, mixing hydroxyethyl-s-triazine, spirocyclic phosphoryl chloride and methanol to obtain a solution D; Step 4, adding the solution D obtained in step 3 dropwise to the solution C obtained in step 2 to react, and after the reaction is completed, centrifuging to remove the supernatant, washing, and vacuum drying to obtain a core pore structure MOF nano flame retardant.

3. The method for preparing a nuclear pore structure MOF nano flame retardant according to claim 2, characterized in that: In the step 1, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 4-8:1; the ratio of 2-methylimidazole to methanol is 1 g:60-120 mL, and the ratio of cobalt nitrate hexahydrate to methanol is 1 g:60-120 mL; the vacuum drying pressure is 0.08-0.1 MPa, and the temperature is 60-70° C.

4. The method for preparing a nuclear pore structure MOF nano flame retardant according to claim 2, characterized in that: In the step 2, the ultrasonic dispersion time is 10 to 30 minutes; the ratio of purple ZIF-67 powder to methanol or ethanol is 1 g: 150-200 mL.

5. The method for preparing a nuclear pore structure MOF nano flame retardant according to claim 2, characterized in that: In the step 3, the molar ratio of hydroxyethyl s-triazine to spirocyclic phosphoryl chloride is 2-2.2:3; the ratio of hydroxyethyl s-triazine to methanol is 1 g: 60-120 mL.

6. The method for preparing a nuclear pore structure MOF nano flame retardant according to claim 2, characterized in that: In the step 4, the temperature is controlled by an ice-water bath during the reaction, the temperature of the ice-water bath is 5-10° C., and the mass ratio of hydroxyethyl s-triazine to ZIF-67 is 1:0.5-0.

8.

7. The method for preparing a nuclear pore structure MOF nano flame retardant according to claim 2, characterized in that: The time for adding solution D is 1 to 4 hours; after the addition is completed, continue to react in an ice-water bath for 3 to 6 hours.

Citation Information

Patent Citations

  • Hexaimidazolecyclotriphosphazene flame retardant with surface modified by ZIF-67 nanocrystals and preparation method thereof

    CN110396202A

  • ZIF-67 doped sodium hexa hydroxybenzene sulfonate cyclotriphosphazene flame retardant and preparation method thereof

    CN110483796A

Cited By

  • EVA / POE composite high-resilience foaming material and preparation method thereof

    CN120623628A

  • Eva / poe composite high resilience foam material and preparation method thereof

    CN120623628B